Hipoglikemia yang Diinduksi Alkohol pada Pasien dengan Dugaan Disfungsi Hati Kronis-Kasus di Daerah Terpencil: Laporan Kasus - Berlan Chandra; Widhyanto P. Adhy; Jeffren Bulan (Cermin Dunia Kedokteran, 2025)
Alcohol has profound effects on glucose metabolism. Alcohol-induced hypoglycemia is rare in healthy individuals with good glycogen reserve, but may be life-threatening in individuals with silent chronic liver dysfunction, due to liver inability to manage glucose uptake. A 39-year-old male was admitted to the emergency room with sudden convulsion after taking local alcoholic beverages. A very low blood glucose level and significantly elevated liver enzyme levels were detected. The patient was stable after 3 days of intensive care without repeated phase of hypoglycemia.